The Outer Membrane Proteins OmpA, CarO, and OprD of Acinetobacter baumannii Confer a Two-Pronged Defense in Facilitating Its Success as a Potent Human Pathogen - Uppalapati, Siva R.; Sett, Abhiroop; Pathania, Ranjana (Frontiers in Microbiology, 2020)
Of all the ESKAPE pathogens, carbapenem resistant and multidrug resistant Acinetobacter baumannii is the leading cause of hospital-acquired and ventilator-associated pneumonia. A. baumannii infections are notoriously hard to eradicate due to its propensity to rapidly acquire multitude of resistance determinants and the virulence factor cornucopia elucidated by the bacterium that help it fend off a wide range of adverse conditions imposed upon by host and environment. One such weapon in the arsenal of A. baumannii is the outer membrane protein (OMP) compendium. OMPs in A. baumannii play distinctive roles in facilitating the bacterial acclimatization to antibiotic and host induced stresses, albeit following entirely different mechanisms. OMPs are major immunogenic proteins in bacteria conferring bacteria host-fitness advantages including immune evasion, stress tolerance and resistance to antibiotics and antibacterials. In this review, we summarize the current knowledge of major A. baumannii OMPs and discuss their versatile role in antibiotic resistance and virulence. Specifically, we explore how OmpA, CarO, OprD-like porins mediate antibiotic and amino acid shuttle and host virulence.